PELUANG DAN TANTANGAN PERDATA WAKAF ASET DIGITAL MELALUI METAVERSE - Ismail, Ismail; Putra, Alif Arhanda (JURNAL AKTA YUDISIA, 2024)
Digital technology in the metaverse field has promising potential and economic advantages. Therefore, digital assets such as Non-Fungible Tokens (NFTs), cryptocurrency, and virtual real estate have the potential to become objects of waqf, although there are challenges in the application of civil law. This research aims to analyze the opportunities and challenges of civil waqf for digital assets in the metaverse and to examine the governance of digital asset waqf in the metaverse. Digital assets in the metaverse have the potential to become waqf objects, as emphasized by Islamic law and UU RI Nomor 41 Tahun 2004 Tentang Wakaf, although there are no clear legal regulations governing them. To maximize the benefits of digital asset waqf governance in the metaverse, it is necessary to adapt smart contracts on the blockchain to ensure legal certainty and digital security, as well as appoint a nazhir capable of managing digital assets in the metaverse effectively. Therefore, despite legal challenges, the potential for managing digital waqf in the metaverse is vast, requiring regulations that are more adaptive to technological developments to ensure the sustainability and benefits of waqf for the broader community.Kata Kunci: Waqf, Digital Assets, Metaverse, Civil Law, Islamic Law, Blockchain, NFT, Cryptocurrency, Real Estate Virtual.